Optimizing the Management of Abnormal Liver Function Tests after Orthotopic Liver Transplant: A Systems-Based Analysis of Health Care Utilization. Issue 10 (October 2017) - Russell, Tara A.; Angarita, Stephanie A. K.; Showen, Amy; Agopian, Vatche; Busuttil, Ronald W.; Kaldas, Fady M.
Elevated liver function tests (eLFTs) are a major cause of unplanned readmissions (UR) after orthotopic liver transplantation. Diagnostic workup for eLFTs requires multiple invasive and noninvasive procedures, often done in the inpatient setting to expedite diagnosis, yet consequently resulting in increased costs. In this study, we evaluated eLFT readmissions at a single institution with respect to resource utilization. From 3/2013 to 12/2015, 388 patients underwent orthotopic liver transplantation, resulting in 463 UR totaling 5833 bed days; 87 (18.8%) UR and 929 (15.9%) bed days were for eLFTs. During eLFT-UR all patients underwent repeat laboratory testing, 75 (86.2%) liver ultrasound, 66 (75.8%) liver biopsy, and 17 (19.5%) endoscopic retrograde cholangiopancreatography. Discharge diagnoses were acute cellular rejection (40.2%), transaminitis not otherwise specified (17.2%), biliary complications (16.1%), recurrent hepatitis (11.5%), vascular complications (5.8%), viral hepatitis (5.8%), and steatohepatitis (3.5%). The greatest bed-day utilization was secondary to acute cellular rejection (60.8%) and biliary complications (13.7%). More than 35 per cent of eLFT-UR were due to transaminitis not otherwise specified, steatohepatitis, recurrent or viral hepatitis, none of which necessitate inpatient treatment. In addition, >25 per cent of eLFT-UR bed days were attributed to diagnostic workup. Identifying patients who can undergo expedited outpatient workup and require only outpatient management will result in significantly decreased readmissions, bed days, and hospital costs.